Stable carbon isotope analysis of nucleic acids to trace sources of dissolved substrates used by estuarine bacteria. - Coffin, R B (1990)
The natural abundance of stable carbon isotopes measured in bacterial nucleic acids extracted from estuarine bacterial concentrates was used to trace sources of organic matter for bacteria in aquatic environments. The stable carbon isotope ratios of Pseudomonas aeruginosa and nucleic acids extracted from cultures resembled those of the carbon source on which bacteria were grown. The carbon isotope discrimination between the substrate and total cell carbon from bacterial cultures averaged 2.3% +/- 0.6% (n = 13). Furthermore, the isotope discrimination between the substrate and nucleic acids extracted from bacterial cultures was 2.4% +/- 0.4% (n = 10), not significantly different from the discrimination between bacteria and the substrate. Estuarine water samples were prefiltered through 1-micron-pore-size cartridge filters. Bacterium-sized particles in the filtrates were concentrated with tangential-flow filtration and centrifugation, and nucleic acids were then extracted from these concentrates. Hybridization with 16S rRNA probes showed that approximately 90% of the nucleic acids extracted on two sample dates were of eubacterial origin. Bacteria and nucleic acids from incubation experiments using estuarine water samples enriched with dissolved organic matter from Spartina alterniflora and Cyclotella caspia had stable carbon isotope values similar to those of the substrate sources. In a survey that compared diverse estuarine environments, stable carbon isotopes of bacteria grown in incubation experiments ranged from -31.9 to -20.5%. The range in isotope values of nucleic acids extracted from indigenous bacteria from the same waters was similar, -27.9 to -20.2%. Generally, the lack of isotope discrimination between bacteria and nucleic acids that was noted in the laboratory was observed in the field.(ABSTRACT TRUNCATED AT 250 WORDS)